β-Glucan-Induced Immuno-Modulation: A Role for the Intestinal Microbiota and Short-Chain Fatty Acids in Common Carp - Petit, Jules; de Bruijn, Irene; Goldman, Mark R. G.; van den Brink, Erik; Pellikaan, Wilbert F.; Forlenza, Maria; Wiegertjes, Geert F. (Frontiers in Immunology, 2022)
Dietary supplementation of fish with β-glucans has been commonly associated with immunomodulation and generally accepted as beneficial for fish health. However, to date the exact mechanisms of immunomodulation by β-glucan supplementation in fish have remained elusive. In mammals a clear relation between high fibre diets, such as those including β-glucans, and diet-induced immunomodulation via intestinal microbiota and associated metabolites has been observed. In this study, first we describe by 16S rRNA sequencing the active naive microbiota of common carp intestine. Based on the abundance of the genus Bacteroides, well known for their capacity to degrade and ferment carbohydrates, we hypothesize that common carp intestinal microbiota could ferment dietary β-glucans. Indeed, two different β-glucan preparations (curdlan and MacroGard®) were both fermented in vitro albeit with distinct fermentation dynamics and distinct production of short-chain fatty acids (SCFA). Second, we describe the potential immunomodulatory effects of the three dominant SCFAs (acetate, butyrate and propionate) on head kidney leukocytes, showing effects on both, nitric oxide production and expression of several cytokines (il1b, il6, tnfα and il10) in vitro. Interestingly, we also observed regulation of expression of several gpr40L genes, which were recently as described putative SCFA receptors. Third, we describe how a single in vivo oral gavage of carp with MacroGard® modulated simultaneously, the expression of several pro-inflammatory genes (il1b, il6, tnfα), type I IFN associated genes (tlr3.1, mx3) and three specific gpr40L genes. The in vivo observations provide indirect support to our in vitro data and the possible role of SCFAs in β-glucan induced immunomodulation. We discuss how β-glucan-induced immunomodulatory effects can be explained, at least in part, by fermentation of MacroGard® by specific bacteria, part of the naive microbiota of common carp intestine, and how a subsequent production of SFCAs could possibly explain immunomodulation by β-glucan via SCFA receptors present on leukocytes.